Penentu Perilaku Knowledge Sharing Para Karyawan Minimarket: Pendekatan Kualitatif - Sri Raharso; Sri Surjani Tjahjawati (Jurnal Manajemen Maranatha, 2014)
ABSTRACT: The purpose of this paper is to explore factors affecting knowledge sharing behaviour of workers in the minimarket’s organization in West Java. Knowledge sharing behaviour is the degree to which knowledge worker actuallyshares knowledge with other members of his/her organization. Based on the theory of planned behaviour, we tried to explore determinants of knowledge sharing in minimarket setting. Structural interview was then use to get the factors thatpromote knowledge sharing. This research identified behavioral and psycho-sociotechnological determinants as enablers of knowledge sharing activity.Keywords: knowledge sharing, behavioral, psycho-socio-technological, minimarket